Antibody-dependent enhancement of porcine reproductive and respiratory syndrome virus infection downregulates the levels of interferon-gamma/lambdas in porcine alveolar macrophages in vitro - Zhang, Liujun; Feng, Xing; Wang, Huandi; He, Shaojun; Fan, Hongjie; Liu, Deyi (Frontiers in Veterinary Science, 2023)
Fc gamma receptor-mediated antibody-dependent enhancement (ADE) can promote virus invasion of target cells, sometimes exacerbating the severity of the disease. ADE may be an enormous hurdle to developing efficacious vaccines for certain human and animal viruses. ADE of porcine reproductive and respiratory syndrome virus (PRRSV) infection has been demonstrated in vivo and in vitro. However, the effect of PRRSV-ADE infection on the natural antiviral immunity of the host cells is yet to be well investigated. Specifically, whether the ADE of PRRSV infection affects the levels of type II (interferon-gamma, IFN-γ) and III (interferon-lambdas, IFN-λs) interferons (IFNs) remains unclear. In this study, our results showed that PRRSV significantly induced the secretion of IFN-γ, IFN-λ1, IFN-λ3, and IFN-λ4 in porcine alveolar macrophages (PAMs) in early infection, and weakly inhibited the production of IFN-γ, IFN-λ1, IFN-λ3, and IFN-λ4 in PAMs in late infection. Simultaneously, PRRSV infection significantly increased the transcription of interferon-stimulated gene 15 (ISG15), ISG56, and 2′, 5′-oligoadenylate synthetase 2 (OAS2) in PAMs. In addition, our results showed that PRRSV infection in PAMs via the ADE pathway not only significantly decreased the synthesis of IFN-γ, IFN-λ1, IFN-λ3, and IFN-λ4 but also significantly enhanced the generation of transforming growth factor-beta1 (TGF-β1). Our results also showed that the ADE of PRRSV infection significantly reduced the mRNAs of ISG15, ISG56, and OAS2 in PAMs. In conclusion, our studies indicated that PRRSV-ADE infection suppressed innate antiviral response by downregulating the levels of type II and III IFNs, hence facilitating viral replication in PAMs in vitro. The ADE mechanism demonstrated in the present study furthered our understanding of persistent pathogenesis following PRRSV infection mediated by antibodies.